Examining the Pathway from Maternal Criminal Involvement to Adolescent Delinquency - Chavira, Dina (2014)
As incarceration rates across the United States have continued to rise, there has been growing concern with the unintended consequences that have resulted. This has prompted researchers across multiple disciplines to study the effects of incarceration at the individual, family, community, and societal levels. An important but overlooked factor pertains to extensive multiple social service agency involvement and missed opportunities for intervention. Families involved with the criminal justice system (CJS) are often at risk of involvement with other human service agencies, one agency being the child welfare system (CWS). Little is known about families who fall within these two systems, and neither system is charged with assessing whether families in this group are unique from those involved in either system. The current study aimed to address limitations in previous studies and supplement the literature in relation to families with dual-system involvement. A nationally representative, longitudinal data set was analyzed to examine whether maternal CJS involvement predicted later youth delinquency within the CWS population. The moderating effects of parental monitoring, nonviolent discipline, and timing of maternal arrest were also examined to gain a better understanding of the conditions in which maternal CJS involvement was exacerbated or ameliorated. Maternal CJS involvement was a significant predictor of change in youth delinquency only in the presence of the moderating variables. Youth with maternal CJS involvement experienced decreases in delinquency regardless of monitoring compared to similar youth who experienced more delinquency in the presence of low monitoring. A timing effect was found such that youth whose mothers were arrested 4.5 to 9.5 years ago were more likely to have elevated delinquency scores at the follow-up assessment. The results of the study suggest families with dual-system involvement are distinct from other families in the CWS. Given concerns to the intergenerational transmission of criminality, this study highlights the importance of interagency coordination around policy and interventions so that at-risk families avoid slipping through the cracks of multiple service involvement